Arabidopsis PIZZA has the capacity to acylate brassinosteroids. - Katja Schneider; Christian Breuer; Ayako Kawamura; Yusuke Jikumaru; Atsushi Hanada; Shozo Fujioka; Takanari Ichikawa; Youichi Kondou; Minami Matsui; Yuji Kamiya; Shinjiro Yamaguchi; Keiko Sugimoto (PLoS ONE, 2012)
Brassinosteroids (BRs) affect a wide range of developmental processes in plants and compromised production or signalling of BRs causes severe growth defects. To identify new regulators of plant organ growth, we searched the Arabidopsis FOX (Full-length cDNA Over-eXpressor gene) collection for mutants with altered organ size and isolated two overexpression lines that display typical BR deficient dwarf phenotypes. The phenotype of these lines, caused by an overexpression of a putative acyltransferase gene PIZZA (PIZ), was partly rescued by supplying exogenous brassinolide (BL) and castasterone (CS), indicating that endogenous BR levels are rate-limiting for the growth of PIZ overexpression lines. Our transcript analysis further showed that PIZ overexpression leads to an elevated expression of genes involved in BR biosynthesis and a reduced expression of BR inactivating hydroxylases, a transcriptional response typical to low BR levels. Taking the advantage of relatively high endogenous BR accumulation in a mild bri1-301 background, we found that overexpression of PIZ results in moderately reduced levels of BL and CS and a strong reduction of typhasterol (TY) and 6-deoxocastasterone (6-deoxoCS), suggesting a role of PIZ in BR metabolism. We tested a set of potential substrates in vitro for heterologously expressed PIZ and confirmed its acyltransferase activity with BL, CS and TY. The PIZ gene is expressed in various tissues but as reported for other genes involved in BR metabolism, the loss-of-function mutants did not display obvious growth phenotypes under standard growth conditions. Together, our data suggest that PIZ can modify BRs by acylation and that these properties might help modulating endogenous BR levels in Arabidopsis.